Virtual Simulation as a Teaching Strategy for Basic Life Support in Nursing Education: A Systematic Review - I Putu Juni Andika; Seftiani Utami; Dian Putranto (Journal Of Nursing Practice, 2025)
Background: Certain training programs, like Basic Life Support training, must change to comply with the new social and physical distancing policies. Health care workers, including nursing students, may benefit from Virtual Simulation, instruction, in order to help them meet the Basic Life Suppport competencies. Therefore, innovation in learning methods through virtual simulation is needed to provide interactive and realistic learning experiences, as well as to enhance students’ knowledge, clinical skills, critical thinking, and self-confidence before entering clinical practice." Objectives: To examine the effectiveness of virtual simulation as a learning approach for Basic Life Support among nursing students. Methods: The literature search was conducted across several databases, including Google Scholar, databases including ScienceDirect, Web of Science, and PubMed, covering studies published between 2019 and 2023. A total of 4,725 articles were initially identified. After title screening (N = 2,310) and abstract evaluation (n = 703), 75 full-text articles were reviewed. Finally, 15 studies that met the inclusion criteria were analyzed. Both English and Indonesian language publications were considered, following the PRISMA guidelines. Results: Demonstrates the emergence of a new virtual simulation learning model that is combined with video-based instruction. During the course of the eight-hour intervention up to two weeks, several indicators of improvement were noted, including resiliency, self-efficacy, understanding, attitudes, skills, and ability to perform resuscitation. In addition, three articles with statistically significant results indicate that the mixed model is more effective when combined with e-learning websites and computer-based simulations. Three articles discuss that, out of the four blended learning models, the most effective parameter is the understanding capacity. Conclusion: This indicates that BLS training should utilise a virtual simulation learning model that takes infrastructure, facilities and training modules into consideration.